2011
DOI: 10.1590/s1516-05722011000500020
|View full text |Cite
|
Sign up to set email alerts
|

Composição química do óleo essencial de duas amostras de carqueja (Baccharis sp.) coletadas em Paty do Alferes - Rio de Janeiro

Abstract: RESUMO:O Brasil possui em sua flora a maior diversidade genética do mundo, apresentando varias espécies nativas. Dentre as plantas nativas do Brasil encontra-se o gênero Baccharis (família Asteraceae) que possui algumas espécies popularmente conhecidas como carqueja, carqueja amarga ou vassoura. Estas espécies são utilizadas na medicina popular como protetora e estimulante do fígado, para o controle da obesidade, diabetes, hepatite, gastroenterite, digestiva, diurética, depurativa, tônica, antianêmica e anti-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(4 reference statements)
2
3
0
Order By: Relevance
“…Morais and Castanha [46] obtained similar results to those of this study when evaluating the chemical composition of two populations of "carqueja" (Baccharis sp.) in the state of Rio de Janeiro, Brazil.…”
supporting
confidence: 83%
“…Morais and Castanha [46] obtained similar results to those of this study when evaluating the chemical composition of two populations of "carqueja" (Baccharis sp.) in the state of Rio de Janeiro, Brazil.…”
supporting
confidence: 83%
“…Because essential oils are secondary metabolites produced for plant's defense [13], genotypes attacked by wasps with gall formation are likely to produce more essential oil as defense strategy [22]. These results corroborate with Morais and Castanha (2012) [23], who found higher concentrations of monoterpenes in the essential oil of basil attacked by mealybug, and Queiroz-Voltan et al (1995) [24] in Hyptis suaveolens populations attacked by herbivores, which produced larger amounts of essential oil.…”
Section: : Two-dimensional Dendrogram Obtained In the Cluster Analysi...supporting
confidence: 71%
“…There was also an important difference between the ledol content at H1 and at T75 (10.63%) detected during summer. The authors of [46] found a concentration of ledol equal to 13.7% in plants collected in Rio de Janeiro, Brazil, whereas the study in [5] reported a value of 1.30% in the essential oil of B. trimera (Less) DC.…”
Section: Differences In Content and Composition Of Essential Oils Between The Three Harvest Timesmentioning
confidence: 94%
“…Differences between our results and the lower levels observed for other samples in the literature of less than or equal to 1.50% could be linked to the environmental conditions and time of harvest, as well as to water deficits and irrigation management . Several studies based on Eugenia uniflora leaves show that the prevalence of factors, such as seasons, influences the prevalence of oxygenated sesquiterpenes in plants collected during all sampling months and under all chemical variations among the oils [46]. Additionally, the influence of factors such as elevation above sea level, soil type, longitude, and latitude was reflected in the prevalence of sesquiterpenes (83.66%) in Cordia verbanacea and Cordia leucocephala leaves [49].…”
Section: Differences In Content and Composition Of Essential Oils Between The Three Harvest Timesmentioning
confidence: 99%